Construction Safety: Laws, Preventive Guidelines, Accidents and Application on Mobile Phones: Laws, Preventive Guidelines, Accidents and Application on Mobile Phones - Powijit, Jitlada; Damrianant, Jirawat (Princess of Naradhiwas University Journal, 2020)
Construction safety laws in Thailand were compiled by categorizing corresponding provisions from different laws. Injuries and illnesses due to construction operations from 2013 to 2017 were analyzed to formulate preventive guidelines. A mobile application (app) was also developed to promote construction safety. The contents of the application were from the categorization and the analysis performed above. Results were that construction safety laws could be classified into 32 categories. The data analysis revealed several important issues regarding construction accidents. For example, the types of accidents that occurred most frequently were objects falling from heights and materials collapsing. These findings suggested health and work environment management by following methods and standards as legally specified. Employers should provide personal protective equipment for workers’ use at all times. Work training sessions and health check-ups should be scheduled and regularly performed. A new smartphone app, SafetyFIRST, developed in this research should also boost overall safety awareness. The app’s contents cover all of the 32 safety categories. Satisfaction of users of SafetyFIRST application was evaluated for 3 aspects; content, presentation and usage. It was found that the satisfaction was at a high level, receiving 3.70 out of 5.00 marks.